Advanced Exergy Analysis on the Turbofan Engine - Indriyati, Feni; Mahandari, Cokorda Prapti; Yamin, Mohamad (Journal of Novel Engineering Science and Technology, 2024)
Studies on energy utilization underscore the paramount importance of energy, as evidenced by numerous researchers. This research encompasses both conventional and advanced exergy analyses. Advanced exergy analysis aims to ascertain the extent of energy loss in each component, influenced by irreversibility, and to account for component interactions within the system. Furthermore, advanced exergy analysis seeks to enhance the operational efficiency of each engine component. The findings reveal that the combustion chamber exhibits the highest level of energy loss, amounting to 32.817 MW. This energy loss primarily stems from irreversibility triggered by chemical reactions leading to heat transfer. Overall, the study results indicate that the exergy influx from external sources surpasses that generated internally in each component system.